THE CATALYTIC ACTIVITY OF THE BLOOD IN RELATION TO (1) THE FUNCTIONAL SUFFICIENCY OF THE KIDNEYS; (2) PERITONITIS - Winternitz, M. C. (The Rockefeller University Press, 1909)
1. The inhibiting action of urine on catalase depends to a great extent on its reaction. The urine of a nephritic has no greater inhibiting power than normal urine provided the reaction of urines tested is neutral. 2. The catalytic activity of a single rabbit's blood is constant from day to day. 3. There is considerable variation in the catalytic action of the blood of different rabbits. 4. Following ligation of the ureters the catalytic activity of the blood gradually decreases; the tissues of an animal which has died as a result of ligation of the ureters show a decided decrease in catalytic activity, when compared with those of normal animals. 5. Following bilateral nephrectomy the same decline of the catalytic action of the blood is observed as after bilateral ligation of ureters. 6. Following unilateral nephrectomy the catalytic activity of the blood may temporarily fall and then rise above its previous level, or it may fall continuously. Wherever the continuous fall occurs the animal dies. 7. When the kidneys are allowed to function but the urine is drained into the peritoneal cavity there is no change in the catalytic activity of the tissues post-mortem but a marked rise in the catalytic activity of the blood accompanies the resulting peritonitis. 8. The same rise in the catalytic activity of the blood is obtained in experimental bacterial peritonitis. This might be of diagnostic importance in determining early inflammations of the peritoneum. 9. A kidney functioning normally changes substances circulating in the blood into urinary products devoid of any influence on catalase. If the kidney cannot effect this change, these substances remain unaltered in the circulating blood and by their presence inhibit the catalytic activity of the blood and organs. 10. Nephritis (Uranium Nitrate).—A. In acute nephritis there is a marked decrease in the catalytic activity of the blood and of the tissues post-mortem. The decrease in the catalytic activity of the blood may vary directly with the amount of urine excreted. B. With the onset of uræmia the catalytic activity of the blood decreases markedly and follows in a general way the urinary findings, especially the total amount of urine. If the animal recovers the catalase gradually rises. C. Although the catalytic activity of a normal rabbit's blood is constant from day to day, the activity of blood from a rabbit in which an experimental nephritis has been produced oscillates markedly. The catalytic activity of the blood may under certain conditions indicate the functional sufficiency of the kidneys much more accurately than the urinary findings.